Metadata and video games emulation: an effective bond to achieve authentic preservation?. (17th July 2017) - Carta, Giovanni
Abstract : Purpose: The aim of this paper is to rethink the concept of significant properties in relationship to video game emulation. Design/methodology/approach: In this paper, video games are examined as complex digital objects, that is digital objects that are constituted by multiple layers that are interconnected with other objects. Starting from the assumption that metadata are fundamental to individuate the authenticity and accuracy of a complex digital object, the research is based on the analysis of the most recent frameworks that propose a substantial use of metadata to perform gaming emulation. Findings: Technical metadata are being used within emulation frameworks to describe digital environments and objects. Although metadata cannot be considered a definitive solution for preserving significant properties of video games, they should be used in a more extensive way across frameworks. Originality/value: This paper tries to provide insights on video game properties that can help to refine the debate on emulation.